Kawasaki Disease Complicated With Macrophage Activation Syndrome: Case Reports and Literature Review - Jin, Ping; Luo, Yong; Liu, Xi; Xu, Jinji; Liu, Chunyi (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is among the most common forms of vasculitis in children. Macrophage activation syndrome (MAS) is a rare and severe complication of KD. In this study, we retrospectively analyzed three KD patients complicated with MAS who were treated in pediatric intensive care units (PICU) and reviewed the relevant literature. We reported that being male, being over 2 years of age, incomplete KD, intravenous immunoglobulin (IVIG) resistance, or persistent fever for more than 10 days are all highly associated with MAS. Relevant examinations should be performed as early as possible to detect MAS. Patients with KD complicated with MAS are at a high risk of having coronary artery involvement or aneurysm formation, which can be reversed with timely treatment. For KD patients with IVIG resistance, additional treatments should be administrated, including a second dose of IVIG (2 g/kg), glucocorticoids, tumor necrosis factor (TNF) inhibitors, and other immunosuppressive drugs or plasma exchange. Early identification and timely treatment are key points for improving the prognosis of KD patients complicated with MAS.